Fertility enhancing efficacy of Cicer arietinum in male albino mice - Sayed, Amany A; Ali, Atef A.; Mohamed, Hanan R. H. (Cellular and Molecular Biology, 2018)
The present study was conducted to investigate the effect of incorporating Cicer arietinum in the diet on the testicular functions of the male mice. Seventy-two mice were divided equally into four groups that were daily fed a diet containing 0, 20, 30 and 50% of C. arietinum seeds, respectively. After 7, 14 and 21 days of starting the experiments, the mice were anesthetized and euthanized to collect the blood, testes, epididymis and seminal vesicles. The present results showed that the increased percentage of C. arietinum in the diet caused significant elevations in the serum levels of testosterone and luteinizing hormone (LH), sperm concentration, sperm motility as well as the testicular levels of antioxidants including glutathione (GSH), glutathione peroxidase (GPx) and catalase (CAT), in comparison to the controls. On the other hand, marked reductions in the sperm abnormality, testicular levels of malondialdehyde (MDA), the percentage of DNA damage in tail and tail moment (TM) were observed in the mice that received a diet containing C. arietinum as compared to the controls. Both the sperms and testes of the mice fed a diet containing C. arietinum in the diet showed a normal intact appearance of the electrophoresed genomic DNA on agarose, as those of the controls. In conclusion, C. arietinum is not only a safe ingredient in the fast-food but also an enhancer of the testicular functions.